2016
DOI: 10.1017/s0022215116000025
|View full text |Cite|
|
Sign up to set email alerts
|

Sublingual immunotherapy in patients with house dust mite allergic rhinitis: prospective study of clinical outcomes over a two-year period

Abstract: Sublingual immunotherapy with house dust mite extracts, including B tropicalis, is efficacious as a treatment for patients with house dust mite allergic rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…The authors conclude that subcutaneous immunotherapy is effective for house dust mite induced allergy, even 10 years after treatment. This study follows previous research which demonstrated that sublingual immunotherapy with house dust mite extracts is also efficacious for patients with house dust mite allergic rhinitis 7 …”
supporting
confidence: 88%
See 1 more Smart Citation
“…The authors conclude that subcutaneous immunotherapy is effective for house dust mite induced allergy, even 10 years after treatment. This study follows previous research which demonstrated that sublingual immunotherapy with house dust mite extracts is also efficacious for patients with house dust mite allergic rhinitis 7 …”
supporting
confidence: 88%
“…This study follows previous research which demonstrated that sublingual immunotherapy with house dust mite extracts is also efficacious for patients with house dust mite allergic rhinitis. 7 Finally, an article by Luu et al 8 in this month's issue continues the theme of surgical simulation, 9,10 and evaluates a low-fidelity ear surgery simulator for developing otological microsurgical skills in lowresource settings. Simulation has become increasingly popular as a method of training surgeons in lowresource settings, with no risk to patient safety.…”
mentioning
confidence: 99%
“…Studies comparing the efficacy of AIT between pediatric and adult patients are limited. A prospective observational study by Soh and colleagues17 indicated that although improvements in medical scores were greater in children than in adults after SLIT, the differences were not significant. In contrast, our study demonstrated that improvements in TNSS and TCS following HDM-SCIT were significantly greater in pediatric AR patients than in adult AR patients.…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, there has been accumulating evidence for the efficacy and safety of AIT for AR, with several studies demonstrating both short-term efficacy8910 and long-term efficacy, using mainly SLIT 11121314. However, comparatively few studies have reported on the efficacy of AIT in Chinese AR patients, with the available data documenting the efficacy of SLIT in pediatric and adult AR patients 151617. Thus, this study aimed to compare the long-term efficacy and safety of SCIT in children and adults with AR.…”
Section: Introductionmentioning
confidence: 99%
“…SLIT to HDM has also been shown to be effective in HDM AR/C by improving nasal and ocular symptoms, which exceeded World Allergy Organization-established clinical efficacy criteria (≥20% improvement versus placebo) by 8 weeks [46]. In a Singapore study, SLIT to all 3 HDM species was found to be effective following pooled analysis in both children and adults [47]. SQ ALK-Abello HDM SLIT tablet has been approved in 11 European countries and Japan for patients with HDM-induced respiratory allergic disease.…”
Section: House Dust Mite Allergen Immunotherapymentioning
confidence: 99%